TUMOR-DERIVED GDF-15 PREVENTS THERAPY SUCCESS OF CHECKPOINT INHIBITORS BY BLOCKING T-LYMPHOCYTE RECRUITMENT - Haake, Markus; Schaefer, Tina; Haack, Beatrice; Vashist, Neha; Genssler, Sabrina; Harter, Patrick; Martens, Alexander; Wistuba-Hamprecht, Kilian; Wedekink, Florian; Fischer, Birgitt; Mittelbronn, Michel; Levesque, Mitchell; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
Immune checkpoint blockade (ICB) can achieve durable responses in a subgroup of patients with metastatic cancer, only. Poor immune effector cell infiltration into the tumor microenvironment is a major obstacle to successful therapy. Growth and differentiation factor 15 (GDF-15) is a divergent member of the TGF-β superfamily and has been linked to feto-maternal tolerance, anorexia but recently also to potent local immunosuppression under physiologic and pathophysiologic conditions. GDF-15 is overexpressed in a wide variety of tumors and may be key factor produced by tumors to prevent effective immune cell infiltration into the tumor and to potently block checkpoint inhibitor activity.<br
CRIS-Team WoS Importer:2022-04-15